The factors promoting crime of minors (Journal of actual problems of jurisprudence, 2018)
In this article the author considers the main reasons of crime of minors. The crime of minors is a consequence of the certain negative phenomena existing in our society.Key words: crime among minors, the causes of juvenile delinquency, prevention of juvenile delinquency.